Phase-Based Algorithm for Estimation of Time Delay Difference in Ultrasonic Flow Meters With Frequency Modulated Signals - Ronkin, Mikhail; Kalmykov, Aleksey (2019 Ural Symposium on Biomedical Engineering, Radioelectronics and Information Technology (USBEREIT), 2019)
The paper deals with a task of effective estimating time delay difference of linear frequency modulated continuous wave (FMCW) signals obtained in the ultrasonic transit-time flowmeters. The main problem consists in the ambiguity of an initial phase difference between signals up to flow and down to it in the case of high flow rate. The proposed solution is the designed algorithm, which is based on our developed method that was published in the previous papers. The algorithm includes a fine measurement of time delay difference by full phase-to-time relation and coarse measurement of the beat frequency as prior information. As it is shown in the paper, this approach has advantages for signals of the ultrasonic FMCW flowmeters in the case of the wide frequency band of the transmitters. The experimentally obtained results approve the ability of the designed algorithm to overcome the aforementioned ambiguity and approve its advantages in the considered task.